Научные исследования и технические средства для тушения лесных пожаров - Shegelman I. R., Kornilov K. A., Vasilyev A. S. (Innovative technologies in science and education, 2017)
scientific organizations and universities of the country are actively searching for technical solutions to extinguish forest fires. At the same technical decisions of scientists are poorly used in practice. It is necessary to accelerate the creation of a basic tractor with increased cross-country capability with a set of multifunctional modules for performing reforestation, fire extinguishing, road construction.
Keywords: тушение; лесные пожары; forest fires; extinguishing; трактор повышенной проходимости; the tractor of the raised passableness